Challenges in the Practice of Teaching in Costa Rican Basic Education - Jiménez Asenjo, Wendy (2023)
The challenges in the initial and continuing training of teachers at the general basic education level were analyzed from a socio-critical and qualitative perspective, according to the student profile outlined in the Costa Rican educational policy. For this, the findings of the research published by the Ministry of Public Education (MEP in Spanish) in 2022 were analyzed, pointing out that initial teacher training presents a theoretical and practical disarticulation that has negative implications in professional practice; likewise, the curricula of some universities are outdated. It is evident that minister, as the main public employer, must define the characteristics of the teaching staff that need to be hired according to the educational policy student´s profile. Lastly, teacher evaluation needs to be reformed to improve professional training processes.